Welfare analysis and redistributive policies - Olivier Bargain (University of Essex, Institute for Social and Economic Research (ISER), 2017)
Applied welfare analyses of redistributive systems nowadays benefit from powerful tax benefit microsimulation programs combined with administrative data. Arguably, most of the distributional studies of that kind focus on social welfare defined as a function - typically inequality or poverty indices - of household equivalized income. In parallel, economic research has made considerable progress in the measurement of welfare along several dimensions. Distinct but related branches of the literature have attempted (i) to model different behaviour (in a way that matter for incidence and redistribution of tax benefit policies), (ii) to go beyond income, (iii) to better define and estimate equivalence scales, (iv) to open the household black box and measure welfare at the individual level. I suggest a general framework to critically review these streams of literatures and to discuss whether recent advances in each of these fields have been or could be readily operationalized in welfare analyses and policy simulations.
Keywords: C81; D31; H21; H23; H31; 330; welfare analysis; redistributive systems; microsimulation; equivalence scales; collective models